Implementing Aided Augmentative Communication Systems With Persons Having Complex Communicative Needs. Issue 6 (November 2019) - Reichle, Joe; Simacek, Jessica; Wattanawongwan, Sanikan; Ganz, Jennifer
Augmentative and alternative communication (AAC) systems can support communication skills for people with significant developmental disabilities who experience complex communication needs (CCNs). There is a need to tailor best practices in AAC assessment and intervention to create individualized communication systems with this population. In this article, we outline the important components of AAC systems that can be implemented in authentic settings. However, given the limited evidence on AAC interventions specific to people with CCNs, we also identify some priority areas for future inquiry. Among these involve strategies to enhance decision making regarding (a) matching communication mode(s) to learner skills and contextual demands, (b) identifying communicative opportunities and obligations, (c) individualizing aided communication display features, (d) selection of vocabulary specificity, and (e) considering dosage parameters needed to acquire and maintain a communicative repertoire. In addition, we briefly discuss the use of telehealth to enhance intervention capability.